Degrading Organic Micropollutants: The Next Challenge in the Evolution of Biological Wastewater Treatment Processes - Singhal, Naresh; Perez-Garcia, Octavio (Frontiers in Environmental Science, 2016)
Global water scarcity is driving the need for identifying new water source. Wastewater could be a potential water resource if appropriate treatment technologies could be developed. One of the barriers to obtaining high quality water from wastewater arises from the presence of organic micropollutants, which are biologically active at trace levels. Removal of these compounds from wastewater by current physico-chemical technologies is prohibitively expensive. While biological treatment processes are comparatively cheap, current systems are not capable of degrading the wide range of organic micropollutants present in wastewater. As current wastewater treatment processes were developed for treating conventional pollutants present at mg/L levels, degrading the ng/L levels of micropollutants will require a different approach to system design and operation. In this paper we discuss strategies that could be employed to develop biological wastewater treatment systems capable of degrading organic micropollutants.